À qui appartient l'éducation ? Les Écoles de village et les Ju|’hoansi de Nyae Nyae, Namibie - Jennifer Hays (Cahiers de la Recherche sur l'Education et les Savoirs)
The Ju|’hoansi are one of the linguistic and cultural groups in South Africa known collectively as the San. Recognized as the first inhabitants of the region, the San – former hunters and gatherers – are located at the bottom of the socioeconomic hierarchy of the region. One measure of this marginalization is the very low enrollment rates of San in the formal education system. This article describes one attempt to address these issues for the Ju|’hoansi: The Nyae Nyae Village Schools. In several Ju|'hoan villages, children, from the first to the third school year are educated in Ju|’hoansi language and live with their families. However, despite these effors, the Village Schools students drop out when they transfer to the mainstream education system in the fourth year. Why? The answer to this question depends heavily on the perspective taken, and this article discusses three theoretical approaches to indigenous education, in order to analyze the discourses produced about the Village Schools and the problems faced by Ju|'hoan students in the public schools that they join after their first three years of schooling. In the language Ju|’hoansi the term for “teacher” is nxarokxao, which translates as “owner of learning”. Who owns education? How can a marginalized community control its own educational processes? Based on 18 years of research on the Village Schools, and the educational dynamics for marginalized groups in southern Africa, this article argues that the Ju|’hoansi express pedagogically sound opinions about the way forward for their education and development, and they make strategic decisions based on realistic economic options available to them.